Research on Buyer-Supplier Relationship Strategy, Contribution to The Company’s Business Development - Didik Suyatno; Susilo Toto Rahardjo (PT. Publikasiku Academic Solution, 2023)
Supplier-buyer courting method is one of the key elements contributing to the performance of the pharmaceutical enterprise because it affects the capacity of providers to deliver and steady uncooked substances for the producing process.The enterprise faces availability issues of uncooked substances in phrases of time and amount required because of delays in deliver from providers (inconsistent uncooked cloth deliver and delivery), this trouble is getting worst because of low and fluctuating forecast accuracy conditions. The phenomenon of the COVID-19 pandemic also worsened the condition of the availability of raw materials because the pandemic caused a shortage and disruption of raw material supply. This have a look at is a qualitative have a look at with descriptive evaluation from interviews consultant informants of consumers and providers. The cause of have a look at is to research the important thing elements that impact dating techniques between providers and consumers, in the long run contributing to enterprise continuity and performance. The effects of this situation have a look at highlight motivation factors, dedication and obligation factors, consider and reputation factors, courting factors, communique and statistics sharing factors, agreement factors, fine and reliability factors, overall performance evaluation factors, help control factors, and procurement strategies. Factors are key factors in a buyer-dealer courting approach to make sure and make sure the provision of uncooked substances in enough quantity, timeliness and fine, contributing to commercial enterprise continuity and overall performance.